Family Caregivers' Experiences and Changes in Caregiving Tasks During the COVID-19 Pandemic. (September 2021) - Irani, Elliane; Niyomyart, Atsadaporn; Hickman, Ronald L.
The purpose of this descriptive study was to describe family caregivers' experiences and changes in caregiving tasks and approaches during the COVID-19 pandemic. Using web-based strategies, 69 family caregivers of adults with chronic or disabling conditions were recruited and completed an online survey about positive and negative caregiving experiences, and ways in which caregiving has changed. Data were analyzed using descriptive statistics (structured questions) and conventional content analysis (open-ended responses). Participants reported concerns about their loved one's physical and mental health, the limited access to other caregiving sources, and the limited opportunities to maintain personal well-being. Caregiving tasks completed more than usual included providing emotional support, shopping for groceries and essentials, and contacting healthcare providers. Participants modified their caregiving approach by assuming added responsibilities, leveraging technology, and managing a new caregiving routine. Findings indicate that family caregivers experienced additional caregiving challenges and changed caregiving tasks considering the limited resources available.